Anaerobic and photocatalytic treatments of post-hydrothermal liquefaction wastewater using H2O2. (September 2018) - Quispe-Arpasi, Diana; de Souza, Raquel; Stablein, Michael; Liu, Zhidan; Duan, Na; Lu, Haifeng; Zhang, Yuanhui; Oliveira, Alessandra Lopes de; Ribeiro, Rogers; Tommaso, Giovana
Abstract: Hydrothermal liquefaction (HTL) of cyanobacteria is a promising process for energy generation. However, post-HTL wastewater (PHWW) contains high amounts of organic matter and toxic compounds. This study investigated photocatalysis and anaerobic digestion (AD) for the treatment of PHWW from Spirulina conversion. H2 O2 was used as an external oxidant in the photocatalysis or as a pretreatment in the AD process. The effect of different concentrations of H2 O2 was evaluated. Greater CH4 production and higher COD reduction were observed when pre-treated PHWW was used. In the photocatalytic treatment, color and COD reduction reached 93.1% and 23.4%, respectively, with the addition of H2 O2 . When a combination of the oxidative pretreatment and AD was applied, a maximum energy recovery of 66.7% was reached, while the photocatalysis reached a maximum of 61.5%. Use of the best conditions with proper dilutions resulted in higher growths of the Spirulina cultivation compared to that with conventional algal media. Graphical abstract: Unlabelled Image Highlights: Integrating HTL with photocatalysis and AD enhanced the overall energy recovery. The maximum CH4 production was 73.9 NmL with a H2 O2 pre-treated PHWW. Photocatalysis achieved a color reduction of 93.1% with H2 O2 addition. HTL energy recovery enhanced when PHWW was treated with H2 O2 and subjected to AD. Spirulina showed high growth in diluted PHWW treated with photocatalysis and AD.